Preparation method and application of nonmetal P-doped ZnIn2S4 photocatalyst

By doping phosphorus elements in ZnIn2S4, the high cost and toxicity problems of noble metal catalysts in α-trifluoromethylation ketolation reaction are solved, and the efficient catalyzing of styrene trifluoromethyl ketolation under visible light is achieved, and the catalyst stability is high.

CN119680592APending Publication Date: 2025-03-25CHONGQING UNIV OF EDUCATION +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411847686.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

Existing precious metal catalysts have high cost and potential toxicity problems in photocatalyzed α-trifluoromethylation ketolation reactions, and the residues that may be generated during the synthesis pose challenges to the pharmaceutical and materials fields.

Method used

By doping phosphorus (P) elements in ZnIn2S4, a non-metallic P-doped ZnIn2S4 photocatalyst was prepared and applied to the styrene methyl ketolation reaction under visible light.

Benefits of technology

It has achieved efficient catalyzed styrene trifluoromethyl ketolation under visible light, with a conversion rate of more than 99%, and a yield of nearly 28%. At the same time, it has improved the separation efficiency of photogenerated charge carriers and the stability of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005189683880000101
    Figure BDA0005189683880000101
  • Figure BDA0005189683880000111
    Figure BDA0005189683880000111
  • Figure BDA0005189683880000121
    Figure BDA0005189683880000121
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a non-metal P-doped ZnIn2S4 photocatalyst, and the method comprises the following steps: dissolving ZnAc2, InCl3. 4H2O, sodium hypophosphite and thioacetamide in water by a hydrothermal method, carrying out a constant temperature reaction at 120 DEG C for 12 h to obtain P-ZnIn2S4, alternately washing with deionized water and absolute ethyl alcohol, and carrying out vacuum drying, with the molar ratio of sodium hypophosphite to thioacetamide being (0.1-4): 1. The photocatalyst P-ZnIn2S4 prepared by the method is used for photocatalytic styrene trifluoromethyl ketonization for the first time, has a good photocatalytic effect and is stable in photocatalytic property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of photochemistry, and specifically relates to a preparation method of a non-metallic P-doped ZnIn2S4 photocatalyst and application thereof. Background Art

[0002] Organic compounds containing trifluoromethyl (CF3) groups are widely present in pharmaceuticals, functional materials and pesticides, mainly because the CF3 group can significantly affect the physical, chemical and biological properties of the parent molecule. In the past few decades, the preparation of α-trifluoromethyl ketones has become a priority research topic in synthetic chemistry as an important building block for the construction of various fluorinated products. In particular, the direct radical trifluoromethylation strategy driven by photoredox catalysis under visible light irradiation has attracted great interest due to its green and tunable catalytic process. This strategy not only conforms to the principles of green chemistry and sustainable chemistry, but also achieves efficient initiation of organic transformations through single electron transfer (SET) pathways or energy transfer (EnT) pathways. However, the high cost and potential toxicity issues of these noble metal catalysts limit their application in large-scale synthesis. In addition, the residues that may be generated during the synthesis of these catalysts pose a challenge to the pharmaceutical and material fields. Therefore, it is particularly important to realize heterogeneous photocatalytic α-trifluoromethylation ketonization under green and environmentally friendly conditions. In particular, the photocatalytic synthesis of α-trifluoromethylated ketone compounds over metal heterogeneous photocatalysts has not been explored so far.

[0003] At present, bimetallic sulfide semiconductors with layered structures, unique electronic properties and adjustable band arrangements are considered to be ideal candidate materials for photocatalytic reactions. The electronic properties and band structures of these materials can be adjusted by changes in chemical composition and external conditions to optimize their performance in photocatalytic processes. In addition, non-metallic doped ZnIn2S4 can improve the separation efficiency of photogenerated charge carriers and reduce the recombination of electron-hole pairs while maintaining good structural stability, and has been widely studied in the field of photocatalysis.

[0004] Document 1, Zhang KL, Tian L, Yang JF, et al. Pauling-Type Adsorption of O2Induced by Heteroatom Doped ZnIn2S4 for Boosted Solar-Driven H2O2Production[J]. Angew. Chem. Int. Ed, 2024, 63(5), e202317816. It discloses that by doping phosphorus (P) in ZnIn2S4 synthesized by solid / gas phase reaction, the O2 adsorption configuration is regulated, thereby optimizing the oxygen reduction reaction (ORR) path and improving the selectivity and yield of H2O2.

[0005] Document 2, Liu HY, Ai SM, Liu YJ, et al. Enhancing photoelectrochemical performance of ZnIn2S4 by phosphorus doping for sensitive detection of miRNA-155 [J]. Chem. Commun, 2020, 56, 14275-14278. discloses a method of doping phosphorus into the ZnIn2S4 structure by solid / gas phase reaction, mixing In(NO3)3·xH2O aqueous solution (0.5mmol / L) with 0.25mmol Zn(NO3)2, stirring until the suspension is uniform, adding 5mL cysteine ​​solution (0.05mol / L) to the prepared suspension, stirring continuously, then transferring the mixture to a stainless steel reactor lined with polytetrafluoroethylene, heating at 200°C for 18h to obtain a yellow solid. This method uses a solid / gas phase reaction, and the actual P doping amount is not easy to control.

[0006] Literature 3 Feng XR, Chen HJ, Yin HF, et al. Facile Synthesis of P-DopedZnIn2S4 with Enhanced Visible-Light-Driven Photocatalytic Hydrogen Production[J]. molecules, 2023, 28, 4520. discloses a P-doped ZnIn2S4 synthesized by a hydrothermal method, wherein 1.0 mmol Zn(CH3COO)2·2H2O, 2.0 mmol InCl3·4H2O, 4 mmol thioacetamide and 4 mmol sodium hypophosphite are dissolved in 100 mL deionized (DI) water, and reacted at 180°C for 12 h in a stainless steel reactor lined with polytetrafluoroethylene.

[0007] The P-doped ZnIn2S4 prepared by the above-mentioned prior art has not had much research on the regulating factors of P-doping synthesis, and is specifically applied to the hydrogen evolution reaction. The inventors provide a preparation of a photocatalyst ZnIn2S4 with different P-doping amounts and its use in the first photocatalytic styrene methyl ketone reaction under visible light. Summary of the invention

[0008] The purpose of the present invention is to provide a method for preparing a non-metallic P-doped ZnIn2S4 photocatalyst, and the application of the P-ZnIn2S4 prepared by the method in the first catalytic trifluoromethyl ketoneization of styrene under visible light.

[0009] To achieve the purpose of the present invention, the following technical solutions are provided.

[0010] In one embodiment, a method for preparing a non-metallic P-doped ZnIn2S4 photocatalyst of the present invention, wherein the photocatalyst is represented by P-ZnIn2S4, comprises the following steps:

[0011] 1) dissolving anhydrous ZnAc2, InCl3·4H2O, sodium hypophosphite and thioacetamide in deionized water to form a colorless clear solution, and reacting at 120°C;

[0012] 2) After the reaction is completed, the mixture is naturally cooled to room temperature, separated, washed, and vacuum dried to obtain P-ZnIn2S4.

[0013] The molar ratio of sodium hypophosphite to thioacetamide is (0.1-4):1, preferably (0.1-2):1.

[0014] The molar mass volume ratio of InCl3·4H2O to deionized water is 1:(20-60) mol / L, preferably 1 mol:20L.

[0015] The photocatalyst prepared by the method is represented by P-ZnIn2S4-X, wherein X represents the molar ratio of P to S in P-ZnIn2S4 is (0.1-4):1, preferably 0.1-2, and more preferably 0.5.

[0016] X represents the P doping amount, and X specifically represents the molar ratio of P:S=(0.1~4):1 (in order to intuitively express the X value, this article can be simplified to P:S=0.1~4, P:S=0.1~2, P:S=0.5, which has the same meaning as the molar ratio expression in this article).

[0017] Preferably, in the above-mentioned preparation method of the present invention, in step 1), the molar ratio of ZnAc2, InCl3·4H2O to thioacetamide and sodium hypophosphite is 0.5:1:2:(0.2-8).

[0018] Preferably, in the preparation method of the present invention, in step 1), the reaction temperature is 120° C. and the reaction time is 12 h.

[0019] Preferably, in the above-mentioned preparation method of the present invention, in step 1), the amount of synthetic water is 20 mL.

[0020] Preferably, in the preparation method of the present invention, in step 2), the washing is performed by alternating deionized water and anhydrous ethanol three times.

[0021] Preferably, in the above-mentioned preparation method of the present invention, in step 2), the drying temperature is 60°C.

[0022] Preferably, in the above-mentioned preparation method of the present invention, in step 2), the P doping amount in P-ZnIn2S4 is expressed by the molar ratio of sodium thiophosphite to thioacetamide = 1:2, i.e. 0.5.

[0023] Another object of the present invention is to provide a photocatalyst P-ZnI2S4 for photocatalytic conversion of styrene and its derivatives into trifluoromethylacetophenone and its derivatives.

[0024] The use of the present invention, the styrene derivative is selected from methoxystyrene (C9H 10 O), p-fluorostyrene (C8H7 F ), p-bromostyrene (C8H7Br), p-chlorostyrene (C8H7Cl), p-methylstyrene (C9H 10 ), p-nitrostyrene (C8H7NO2), p-cyanostyrene (C9H7N), 4-tert-butylstyrene (C 12 H 16 ), m-chlorostyrene (C8H7Cl) and 2-vinylnaphthalene (C 12 H8).

[0025] The use of the present invention is to use it as a photocatalyst in the reaction of acetophenone or its derivatives with sodium trifluoromethanesulfite in an organic solvent to generate trifluoromethylacetophenone and its derivatives; preferably, the organic solvent is acetonitrile or acetone. Preferably, in the use of the present invention, the photocatalyst P-ZnI2S4 is prepared by the preparation method of the present invention.

[0026] In a specific embodiment, the preparation method of the P-doped ZnI2S4 photocatalyst of the present invention comprises the following steps:

[0027] 1) Dissolve ZnAc2, InCl3, thioacetamide and sodium hypophosphite in deionized water, stir and mix at room temperature for 30 minutes, and react at 120°C;

[0028] 2) After the reaction is completed, the mixture is naturally cooled to room temperature, washed, and vacuum dried to obtain photocatalysts P-ZnIn2S4-X with different P doping amounts, wherein X represents the P doping amount, and X specifically represents a molar ratio of P:S = (0.1-4): 1 (which can be simplified as P:S = 0.1-4 in this article).

[0029] Wherein, in step 1), the molar ratio of ZnAc2, InCl3, thioacetamide and sodium hypophosphite is 0.5:1:2:(0.2-8) characterized in that the molar mass volume ratio of InCl3·4H2O to deionized water is 1mmol:(20-60)ml.

[0030] The above preparation method of the present invention prepares the photocatalyst P-ZnIn2S4-X, where X represents different molar ratios of P:S, specifically P:S=0.1~4, such as P-ZnIn2S4-0.1, P-ZnIn2S4-0.3, In2S4-0.5, P-ZnIn2S4-4, etc.

[0031] Preferably, in the preparation method of the present invention, X is 0.1, 0.3, 0.5, 1, 1.5, or 2.

[0032] Preferably, in the preparation method of the present invention, InCl3 is InCl3·4H2O, and the molar mass volume ratio of InCl3 to deionized water is 1mmol:(20-60)ml, preferably 1mmol:20ml.

[0033] Preferably, in the preparation method of the present invention, the reaction is carried out in a stainless steel reactor lined with polytetrafluoroethylene, and the reaction temperature is 120° C. and the reaction time is 12 h.

[0034] Preferably, in the preparation method of the present invention, in step 2), the washing is performed by alternating deionized water and anhydrous ethanol three times.

[0035] Preferably, in the above-mentioned preparation method of the present invention, in step 2), the drying temperature is 60°C.

[0036] In another embodiment, the method also provides a method for preparing ZnIn2S4 by the preparation method of the present invention for use in styrene, methoxystyrene (C9H 10 O), p-fluorostyrene (C8H7F), p-bromostyrene (C8H7Br), p-chlorostyrene (C8H7Cl), p-methylstyrene (C9H 10 ), p-nitrostyrene (C8H7NO2), p-cyanostyrene (C9H7N), 4-tert-butylstyrene (C 12 H 16 ), m-chlorostyrene (C8H7Cl), 2-vinylnaphthalene (C12 H8) were photocatalytically converted into their respective corresponding trifluoromethylacetophenones.

[0037] Preferably, in the above-mentioned use of the present invention, the reaction of styrene, methoxystyrene or p-fluorostyrene with sodium trifluoromethanesulfite to produce acetophenone, methoxytrifluoromethylacetophenone and p-fluorotrifluoromethylacetophenone under the catalysis of the photocatalyst of the present invention is carried out in a solvent of acetonitrile or acetone.

[0038] In a specific embodiment, a method for preparing a P-doped ZnIn2S4 photocatalyst of the present invention comprises the following steps:

[0039] 1) ZnAc2, InCl3·4H2O, thioacetamide and sodium hypophosphite were dissolved in 40 mL or 20 mL of deionized water in a molar ratio of 0.5:1:2:(0.2, 0.6, 1, 2, 3, 4, 6, 8) mmol, respectively, to obtain a mixed solution, which was transferred to a stainless steel reactor lined with polytetrafluoroethylene and reacted at 120°C for 12 hours.

[0040] 2) After the reaction is completed, the reactor is cooled to room temperature, the solution is poured out and washed alternately with deionized water and anhydrous ethanol three times, and then vacuum dried to obtain non-metallic P-doped photocatalysts P-ZnIn2S4-0.1, P-ZnIn2S4-0.3, P-ZnIn2S4-0.5, P-ZnIn2S4-1, P-ZnIn2S4-0.1.5, P-ZnIn2S4-2, P-ZnIn2S4-3, and P-ZnIn2S4-4.

[0041] Preferably, in the preparation method of the present invention, in step 1), the molar mass volume ratio of InCl3 to deionized water is 1 mmol:20 ml; in step 1), the molar ratio of thioacetamide to sodium hypophosphite is 2:1; in step 2), the washing and the drying are performed at a drying temperature of 60°C and vacuum dried for 2 hours.

[0042] Preferably, the present invention discloses an improved preparation method of a non-metallic P-doped ZnI2S4 photocatalyst P-ZnInS-0.5, comprising the following steps:

[0043] (1) ZnAc2, InCl3·4H2O, thioacetamide and sodium hypophosphite are dissolved in deionized water in a molar ratio of 0.5:1:2:1, wherein the molar mass volume ratio of InCl3·4H2O to deionized water is 1 mmol:20 ml.

[0044] (2) The mixed solution was transferred to a stainless steel reactor lined with polytetrafluoroethylene and reacted at 120°C for 12 hours;

[0045] (3) After the reaction, the reactor was cooled to room temperature naturally to obtain a yellow suspension, which was then washed alternately with deionized water and anhydrous ethanol for three times each, and dried under vacuum at 60° C. for 10 h to obtain a non-metallic P-doped photocatalyst P-ZnInS-0.5.

[0046] Beneficial effects of the present invention: The preparation method of the present invention is an improved scheme based on the preparation method of the existing document 3. The key points of the improvement are the reaction temperature and the amount of P doping. However, it is surprisingly found that the photocatalyst P-ZnIn2S4 prepared by the improved method has good photocatalytic performance for the trifluoromethyl ketone reaction of styrene.

[0047] Under visible light, the P-ZnIn2S4 (i.e., P-ZnInS-0.5) prepared by the method of the present invention has excellent catalytic performance for the dehydrogenation and trifluoromethyl ketone of styrene, and the conversion rate of styrene reaches more than 99% within 5 hours, while the yield of trifluoromethyl acetophenone is close to 28%. Through the analysis of the photocatalytic mechanism, the study shows that in the environment of Air, styrene is used as a raw material, CF3SO2Na is used as a fluorine source, and the trifluoromethyl acetophenone compound is formed through the synergistic free radical addition of photogenerated holes, superoxide anion radicals and singlet oxygen. At the same time, electrochemical tests also show that the photogenerated hole utilization rate and photogenerated carrier separation efficiency of P-ZnInS-0.5 are very high. The catalyst can efficiently catalyze the dehydrogenation and trifluoromethyl ketone of styrene, and can be recycled, with stable catalytic properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 Characterization images of the photocatalyst P-ZnIn2S4-0.5 prepared in Example 1, wherein (ab) are scanning electron microscope (SEM) images and field emission transmission electron microscope (TEM) images of ZnIn2S4, and (b) are scanning electron microscope (SEM) images and field emission transmission electron microscope (TEM) images of P-ZnInS-0.5;

[0049] Figure 2 These are test graphs of ZnIn2S4 and the photocatalyst P-ZnIn2S4-0.5 prepared in Example 1, wherein (ab) are Mott-Schottky test graphs of ZnIn2S4 and P-ZnIn2S4-0.5, and (cd) are UV-visible diffuse reflection absorption spectra and Tuac graphs of ZnIn2S4 and P-ZnIn2S4-0.5;

[0050] Figure 3 This is a test diagram of the specific surface area of ​​ZnIn2S4 and photocatalyst P-ZnIn2S4-0.5 prepared in Example 1;

[0051] Figure 4Photocurrent response (IT) graph of the photocatalysts P-ZnIn2S4-0 and P-ZnIn2S4-0.5 prepared in Example 1;

[0052] Figure 5 XRD comparison diagram of the photocatalyst ZnIn2S4 prepared in Example 1 before and after the catalytic reaction;

[0053] Figure 6 This is the XRD comparison diagram of the photocatalyst P-ZnIn2S4-0.5 prepared in Example 1 before and after the catalytic reaction. DETAILED DESCRIPTION

[0054] The following examples are typical and are used to help understand and further illustrate the essence of the present invention, but are not intended to limit the scope of the present invention.

[0055] Example 1 Preparation of Photocatalyst P-ZnIn2S4-0.5

[0056] The preparation process is as follows:

[0057] 1) Add 20 mL of deionized water to a beaker, weigh 0.5 mmol ZnAc2, 1 mmol InCl3·4H2O, 2 mmol thioacetamide (TAA) and 1 mmol sodium hypophosphite (NaH2PO2) and add them to the beaker respectively, stir and dissolve into a colorless clear solution to obtain a mixed solution;

[0058] 2) The mixed solution was transferred to a stainless steel reactor lined with polytetrafluoroethylene and reacted at 120°C for 12 hours;

[0059] 3) After the reaction is completed, the reactor is naturally cooled to room temperature to obtain a yellow suspension, which is centrifuged to obtain a yellow solid, which is then washed alternately with deionized water and anhydrous ethanol for 3 times each, and vacuum dried at 60°C for 10 hours to obtain a non-metallic P-doped ZnIn2S4 photocatalyst P-ZnIn2S4-0.5.

[0060] Referring to the above method, except that sodium hypophosphite is not added, P-ZnIn2S4-0 (i.e. ZnIn2S4) is obtained.

[0061] The prepared P-ZnIn2S4-0 (i.e. ZnIn2S4) and P-ZnIn2S4-0.5 were tested by scanning electron microscopy and field emission transmission electron microscopy:

[0062] A small amount of the obtained products P-ZnIn2S4-0 and P-ZnIn2S4-0.5 were taken and placed in an agate mortar for thorough grinding. The samples were then characterized by environmental scanning electron microscopy (SEM, Thermo Fisher Scientific, Quattro S) and field emission electron microscopy (TEM, ThermoFisher Scientific, Talos F200S) for material morphology. The SEM test results are shown in Figure 2. Figure 1 (a)(c), TEM test results are as follows Figure 1 (b)(d) As shown in the TEM images, P-ZnIn2S4-0 and P-ZnIn2S4-0.5 are multilayer nanosheet structures.

[0063] The prepared P-ZnIn2S4-0 and P-ZnIn2S4-0.5 were subjected to Mott-Schottky test:

[0064] 10 mg of the synthesized sample was added to a mixed solution containing 230 μL of deionized water, 250 μL of anhydrous ethanol, and 20 μL of Nafion solution to prepare a slurry. 10 μL of the slurry was taken and applied to an ITO conductive glass (10 mm × 10 mm × 1 mm) to prepare a sheet. The test was performed using a DH7006 electrochemical workstation. The results are shown in FIG. Figure 2 As shown in (ab), the flat band potential E of ZnIn2S4 fb =-0.57 V vs SCE (-0.33 V vs RHE). Using the formula ECB = Efb-0.1, the conduction band (CB) of the catalyst is calculated to be -0.43 V vs RHE. The flat band potential E fb It is -0.60 V vs SCE (-0.36 V vs RHE). Using the formula ECB=Efb-0.1, the conduction band (CB) of the catalyst is calculated to be -0.46 V vs RHE.

[0065] The prepared P-ZnIn2S4-0 and P-ZnIn2S4-0.5 were subjected to UV-visible diffuse reflection test:

[0066] Take the prepared P-ZnIn2S4-0 and P-ZnIn2S4-0.5 and put them into 1cm 2 The solid UV-Vis diffuse reflectance spectrometer UV-2700i UV-Vis-NIR was used to test the disk. The results are as follows Figure 2As shown in (cd), the results show that the prepared P-ZnIn2S4-0 and P-ZnIn2S4-0.5 absorb visible light. The band gaps of P-ZnIn2S4-0 and P-ZnIn2S4-0.5 are 2.68 V and 2.62 V, respectively, obtained by the formula 1240 / λ. By subtracting the conduction band from the band gap, the valence band (VB) of ZP-ZnIn2S4-0.5 is 2.16 V vs RHE.

[0067] The prepared P-ZnIn2S4-0 and P-ZnIn2S4-0.5 were subjected to BET test:

[0068] The specific surface area (BET) of the catalysts P-ZnIn2S4-0 and P-ZnIn2S4-0.5 was determined using a fully automatic multi-station specific surface and pore size analyzer (MicrotracBEL, Japan). 500 mg of the ZnIn2S4 sample to be tested was placed in a sample tube. The sample tube was installed in the degassing station. When installing the sample tube, the sample tube must be aligned with the port and the screws must be tightened to ensure a safe seal. Then the heating pack was put on the sample tube, and the parameters such as file information and degassing temperature were set. The vacuum pump was turned on and the sample was heated and vacuum degassed to remove the gas adsorbed on the surface of the material. After the degassing was completed, the heating power was turned off, and after the sample cooled to room temperature, nitrogen was backfilled and the gross weight of the sample was weighed. The same sample tube, stopper and filling rod were used for the following work. The sample was weighed using the reduction method to obtain the sample mass. The weighed sample tube was installed in the analysis station, the test parameters were set, and the adsorption and desorption test process was started. After the test, the sample in the sample tube was removed. Wash the sample tube and dry it for later use. The test results are shown in Figure 3 .

[0069] The prepared P-ZnIn2S4-0 and P-ZnIn2S4-0.5 were subjected to IT test:

[0070] The photocurrent response (IT) test was carried out on a DH7006 electrochemical workstation (Donghua, Jiangsu). Figure 4 shown.

[0071] Example 2 Preparation of P-ZnIn2S4-X (X = 0.1, 0.3, 1, 1.5, 2, 3)

[0072] 1. Preparation of P-ZnIn2S4-0.1

[0073] The method of Example 1 was used for preparation, except that the amount of sodium hypophosphite in Example 1 was replaced by 0.2 mmol to obtain a non-metallic P-doped photocatalyst P-ZnIn2S4-0.1.

[0074] 2. Preparation of P-ZnIn2S4-0.3

[0075] The photocatalyst P-ZnIn2S4-0.3 was prepared by referring to the method of the aforementioned document 1, and the amount of sodium hypophosphite was 0.6 mmol.

[0076] 3. Preparation of P-ZnIn2S4-1

[0077] The photocatalyst P-ZnIn2S4-1 was prepared by referring to the method of the aforementioned document 1, and the amount of sodium hypophosphite was 2 mmol.

[0078] 4. Preparation of P-ZnIn2S4-1.5

[0079] The photocatalyst P-ZnIn2S4-1.5 was prepared by referring to the method of the aforementioned document 1, and the amount of sodium hypophosphite was 3 mmol.

[0080] 5. Preparation of P-ZnIn2S4-2

[0081] The photocatalyst P-ZnIn2S4-2 was prepared by referring to the method of the aforementioned document 1, and the amount of sodium hypophosphite was 4 mmol.

[0082] 6. Preparation of P-ZnIn2S4-3

[0083] The photocatalyst P-ZnIn2S4-3 was prepared by referring to the method of the aforementioned document 1, and the amount of sodium hypophosphite was 6 mmol.

[0084] 7. Preparation of P-ZnIn2S4-4

[0085] The photocatalyst P-ZnIn2S4-4 was prepared by referring to the method of the aforementioned document 1, and the amount of sodium hypophosphite was 8 mmol.

[0086] Example 3 Preparation of P-ZnIn2S4-0.5 at different synthesis temperatures and synthesis water amounts

[0087] 1. Prepared by referring to the method of Example 1, except that the synthesis temperature and the amount of synthesis water in Example 1 were replaced with 120° C. and 20 mL, to obtain the non-metallic P-doped photocatalyst P-ZnIn2S4-0.5.

[0088] 2. Prepared by referring to the method of Example 1, the synthesis temperature and the amount of synthesis water were replaced with 120°C and 40 mL to obtain the non-metallic P-doped photocatalyst P-ZnIn2S4-0.5.

[0089] 3. Prepared by referring to the method of Example 1, the synthesis temperature and the amount of synthesis water were replaced with 120°C and 60 mL to obtain the non-metallic P-doped photocatalyst P-ZnIn2S4-0.5.

[0090] 4. Prepared by referring to the method of Example 1, the synthesis temperature and the amount of synthesis water were changed to 140°C and 20 mL, and the non-metallic P-doped photocatalyst P-ZnIn2S4-0.5 was obtained.

[0091] 5. Prepared by referring to the method of Example 1, the synthesis temperature and the amount of synthesis water were changed to 140°C and 40 mL, and the non-metallic P-doped photocatalyst P-ZnIn2S4-0.5 was obtained.

[0092] 6. Prepared by referring to the method of Example 1, the synthesis temperature and the amount of synthesis water were replaced with 140°C and 60 mL to obtain the non-metallic P-doped photocatalyst P-ZnIn2S4-0.5.

[0093] 7. Prepared by referring to the method of Example 1, the synthesis temperature and the amount of synthesis water were replaced with 160°C and 20 mL to obtain the non-metallic P-doped photocatalyst P-ZnIn2S4-0.5.

[0094] 8. Prepared by referring to the method of Example 1, the synthesis temperature and the amount of synthesis water were changed to 160°C and 40 mL, and the non-metallic P-doped photocatalyst P-ZnIn2S4-0.5 was obtained.

[0095] 9. Prepared by referring to the method of Example 1, the synthesis temperature and the amount of synthesis water were changed to 160°C and 60 mL, and the non-metallic P-doped photocatalyst P-ZnIn2S4-0.5 was obtained.

[0096] 10. Prepared by referring to the method of Example 1, the synthesis temperature and the amount of synthesis water were replaced with 180°C and 20 mL to obtain the non-metallic P-doped photocatalyst P-ZnIn2S4-0.5.

[0097] 11. Prepared by referring to the method of Example 1, the synthesis temperature and the amount of synthesis water were changed to 180°C and 40 mL, and the non-metallic P-doped photocatalyst P-ZnIn2S4-0.5 was obtained.

[0098] 12. Prepared by referring to the method of Example 1, the synthesis temperature and the amount of synthesis water were replaced with 180°C and 60 mL to obtain the non-metallic P-doped photocatalyst P-ZnIn2S4-0.5.

[0099] Example 4 Application Effect Test

[0100] 1. Trifluoromethyl ketone activity test of styrene

[0101] The P-ZnIn2S4 prepared in Examples 1 and 2 was used to perform an experiment on photocatalytic conversion of styrene into trifluoromethylacetophenone. The specific steps of the experiment are as follows:

[0102] 50 mg of the photocatalyst P-ZnIn2S4 prepared in Examples 1 and 2 were placed in a 20 mL quartz glass reaction vessel equipped with a magnetic stirring bar, and styrene (0.50 mmol), sodium trifluoromethanesulfinate (1.0 mmol) and ACN (10 mL) were added. The reaction vessel was exposed to LED (420-430 nm, 50 W) irradiation at room temperature and air and stirred for 5 h. Trifluoromethylacetophenone was obtained. The non-metallic P-doped photocatalysts P-ZnIn2S4-0, P-ZnIn2S4-0.1, P-ZnIn2S4-0.3, P-ZnIn2S4-0.5, P-ZnIn2S4-1, P-ZnIn2S4-1.5, P-ZnIn2S4-2, P-ZnIn2S4-3, and P-ZnIn2S4-4 prepared in Example 1 and Example 2 were used to photocatalyze the reaction of styrene with sodium trifluoromethanesulfinate to generate trifluoromethylacetophenone in ACN solvent. The yield (HPLC yield) of each catalyst is shown in Table 1.

[0103] Table 1. Yields of P-ZnIn2S4-X catalytic reactions

[0104]

[0105] b is HPLC yield, NR is unreacted

[0106] The results in Table 1 show that the yields of P-ZnIn2S4-0.5 and P-ZnIn2S4-1.5 catalysts reached 28% and 27%, respectively, which showed higher catalytic efficiency than P-ZnIn2S4-0.1 (19%), P-ZnIn2S4-0.3 (18%), P-ZnIn2S4-0.1 (18.%), P-ZnIn2S4-2 (21%), P-ZnIn2S4-3 (11.%), and P-ZnIn2S4-4 (13.%). This shows that in the P-ZnIn2S4 catalyst, the appropriate phosphorus doping ratio can significantly improve the yield of the catalytic reaction. Figure 4 The photocurrent response diagram (IT) shows that the photogenerated carrier separation efficiency of P-ZnIn2S4 is significantly greater than that of the parent ZnIn2S4, indicating that P doping can effectively promote the transfer of photogenerated charges to enhance the photocatalytic performance. Although the yield of the parent ZnIn2S4 effect also reached 28%, by comparing the XRD diagrams of ZnIn2S4 before and after catalysis (see Figure 5 ) found that there was a serious photocorrosion phenomenon, and S single impurities would appear after the catalytic reaction. Therefore, the phase structure of the catalyst with good stability can be obtained by P-doping the photocatalyst P-ZnIn2S4.

[0107] 2. The trifluoromethyl ketone activity of P-ZnIn2S4-0.5 in styrene under different synthesis water amounts and temperature conditions. The results are shown in Table 2.

[0108] Table 2. Yields of catalytic reactions of P-ZnIn2S4-X with different amounts of synthesis water

[0109]

[0110] Table 2 shows the non-metallic P-doped photocatalyst P-ZnIn2S4-0.5 prepared in Example 1, using different amounts of synthesis water and temperatures to carry out photocatalytic trifluoromethyl ketone reaction of styrene in CH3CN. The results show that when the synthesis temperature is 120°C and the amount of synthesis water is 20 mL, the photocatalyst P-ZnIn2S4 exhibits the best photocatalytic performance.

[0111] 3. The trifluoromethyl ketone activity of P-ZnIn2S4-0.5 in different solvents.

[0112] Due to different solvents, HPLC test is relatively difficult. Substrate 1a is replaced with p-methoxystyrene, and the separation yield is adopted. 50 mg of the photocatalyst P-ZnIn2S4-0.5 prepared in Example 1 is added to a 20 mL quartz glass reaction vessel equipped with a magnetic stirring bar, and p-methoxystyrene (0.50 mmol), sodium trifluoromethanesulfinate (1.0 mmol) and solvent (10 mL) are added. The reaction vessel is exposed to LED (420-430 nm, 50 W) irradiation at room temperature and stirred for 5 h. Trifluoromethylacetophenone is obtained. The yield (HPLC yield) of each catalyst is shown in Table 1. Referring to the method in 1 above, sodium trifluoromethanesulfinate reacts in different solvents to generate p-methoxytrifluoromethylacetophenone (3a) and 1-p-methoxy-4-(3,3,3-trifluoromethyl-1-ene)benzene (4a). The results are shown in Table 3.

[0113] Table 3. Catalytic effect of P-ZnIn2S4-0.5 in different solvents

[0114]

[0115] Table 3 shows the photocatalytic trifluoromethyl ketoneation of p-methoxystyrene by the non-metallic P-doped photocatalyst P-ZnIn2S4-0.5 prepared in Example 1 in different solvents. By comparing the effects of CH3OH (10.7%), DMSO (5.29%), DMF (13.44%), THF (trace), DCM (26%), and PhCF3 (10.7%) as solvents, the results show that the reaction of P-ZnIn2S4-0.5 in CH3CN (26%) and Acetone (26.6%) shows a higher yield.

[0116] The catalyst P-ZnIn2S4-0.5 after the catalytic oxidation experiment was recovered and XRD was performed, and compared with the XRD before the catalytic oxidation experiment. The results are shown in Figure 6 , P-ZnIn2S4-0.5 catalyzes the trifluoromethyl ketone reaction of styrene solution under visible light. As can be seen from the figure, the XRD pattern of the sample after the reaction is consistent with the XRD pattern of the initially prepared sample, indicating that P-ZnIn2S4-0.5 has high stability.

[0117] From the above experimental results, it can be seen that the non-metallic P-doped photocatalyst P-ZnIn2S4-0.5 synthesized and prepared in Example 1 has a high conversion rate and good yield for the trifluoromethyl ketone of styrene. The performance of the P-ZnIn2S4-0.5 photocatalyst is evaluated by a reaction containing styrene (0.50mmol), sodium trifluoromethanesulfinate (1.0mmol) and ACN (10mL). The experimental results show that within 5H, the yield of the photocatalytic trifluoromethyl ketone of styrene can reach 28%.

[0118] 4. Substrate expansion and application

[0119] Referring to the experimental method for trifluoromethyl ketoneization of styrene in 1 above, the non-metallic P-doped photocatalyst P-ZnIn2S4-0.5 prepared in Example 1 was subjected to photocatalytic oxidation under visible light to react styrene with different substituents with sodium trifluoromethanesulfinate to generate trifluoromethyl acetophenone derivatives. This experiment was used to verify the photocatalytic efficiency of P-ZnIn2S4-0.5 on styrene with different substituents. The results are shown in Table 4.

[0120] Table 4. Catalytic performance of P-ZnIn2S4-0.5 on different substrates

[0121]

[0122] The results in Table 4 show that P-ZnIn2S4-0.5 has excellent photocatalytic performance for styrene (styrene derivatives) with different substituents.

Claims

1. A method for preparing a P-doped ZnIn2S4 photocatalyst, wherein the photocatalyst is P-ZnIn2S4-X, in, X represents a molar ratio of P:S of 0.1 to 4. The method comprises the following steps: 1) dissolving anhydrous ZnAc2, InCl3·4H2O, sodium hypophosphite and thioacetamide in deionized water to form a solution, and reacting at 120°C; 2) After the reaction is completed, the mixture is naturally cooled to room temperature, separated, washed, and vacuum dried to obtain P-ZnIn2S4. Wherein, the molar ratio of sodium hypophosphite to thioacetamide is (0.1-4):1, preferably (0.1-2):1; The molar mass volume ratio of InCl3·4H2O to deionized water is 1:(20-60) mol / L, preferably 1:20 mol / L.

2. The preparation method according to claim 1, wherein in step 1), the molar ratio of ZnAc2, InCl3·4H2O to thioacetamide is 0.5:1:

2.

3. The preparation method according to claim 1, wherein X represents a molar ratio of P:S of 0.1 to 2, preferably 0.

5.

4. The preparation method according to claim 1, wherein in step 1), the reaction time is 12 h.

5. The preparation method according to claim 1, in step 2), the washing comprises washing with deionized water and anhydrous ethanol alternately three times.

6. The preparation method according to claim 1, wherein in step 2), the drying temperature is 60°C.

7. Use of the photocatalyst P-ZnIn2S4-X for photocatalytic conversion of styrene and its derivatives into trifluoromethylacetophenone and its derivatives, wherein: X represents that the molar ratio of P:S is 0.1 to 4, preferably 0.1 to 2, and more preferably 0.

5.

8. The use as claimed in claim 7, wherein the styrene derivative is selected from methoxystyrene (C9H 10 O), p-fluorostyrene (C8H7F), p-bromostyrene (C8H7Br), p-chlorostyrene (C8H7Cl), p-methylstyrene (C9H 10 ), p-nitrostyrene (C8H7NO2), p-cyanostyrene (C9H7N), 4-tert-butylstyrene (C 12 H 16 ), m-chlorostyrene (C8H7Cl) and 2-vinylnaphthalene (C 12 H8).

9. The use according to claim 7 or 8, which refers to the use as a photocatalyst in the reaction of acetophenone or its derivatives with sodium trifluoromethanesulfite in an organic solvent to generate trifluoromethylacetophenone and its derivatives; preferably, the organic solvent is acetonitrile or acetone.

10. The use according to any one of claims 7 to 9, wherein the photocatalyst P-ZnI2S4-X is prepared by the preparation method according to claims 1 to 6.